Presepsin (Soluble CD14 Subtype): Reference Ranges of a New Sepsis Marker in Term and Preterm Neonates - Pugni, Lorenza; Pietrasanta, Carlo; Milani, Silvano; Vener, Claudia; Ronchi, Andrea; Falbo, Mariella; Arghittu, Milena; Mosca, Fabio (PloS one, 2015)
Presepsin (soluble CD14 subtype) has been shown to be beneficial as a sepsis marker in adults. Nevertheless, very few data are available in neonates. The aim of the present study was to determine reference ranges of presepsin in term and preterm neonates. Healthy term neonates and preterm neonates without clinical signs of infection admitted to the Neonatal Unit were consecutively enrolled. Presepsin concentrations in whole blood were measured using a point-of-care assay system located in the Unit. Demographic data, antenatal and perinatal variables commonly affecting C-reactive protein and procalcitonin values were considered. Of the 684 neonates enrolled in the study, 484 (70.8%) were born at term and 200 (29.2%) were preterm (24-36 weeks' gestation). In term infants, presepsin median value was 603.5 pg/mL (interquartile range: 466.5-791 pg/mL; 5th and 95th centiles: 315 and 1178 pg/mL respectively). In preterm infants, presepsin median value was slightly higher, equal to 620 pg/mL (interquartile range: 503-864 pg/mL; 5th and 95th centiles: 352 and 1370 pg/mL respectively). The reference ranges of presepsin we determined were much higher than those seen in healthy adults. No correlation between presepsin levels and postnatal age was observed, as well as no significant difference was demonstrated in preterm neonates at different gestational ages. None of the variables analyzed affected presepsin levels at a clinical significant extent. For the first time, this study provides reference ranges of presepsin in term and preterm neonates. Having reliable reference values is crucial for obtaining an adequate diagnostic accuracy. Based on our results, most variables commonly affecting C-reactive protein and procalcitonin values do not affect presepsin levels, which suggests that presepsin could be an effective sepsis marker. Further investigations in large groups of neonates with sepsis are needed to determine the diagnostic and prognostic value of this biomarker.